Impact of Leadership on Educational Governance: A Second-Order Analysis in Mexican Public Teacher Training Colleges - Mendoza-Martinez, Ignacio Alejandro; Garcia-Rivera, Blanca Rosa; Nava, Victor Xochitotol (Journal of Ecohumanism, 2025)
The purpose of this study was to determine the effect of transformational, transactional, and laissez-faire leadership subscales on the outcome variables (satisfaction, extra effort, and leadership effectiveness) in Public Teaching Schools in Mexico, using Bass and Avolio's theoretical model and second order structural modeling with latent variables (composites). A sample of 1,515 teaching and administrative staff was administered the "Worker's Sociodemographic and Organizational Data Questionnaire" and the "Adaptation to the Multifactor Leadership Questionnaire" (MLQ). The second-order Structural Equation Models enabled graphic and statistical analysis of the influence of leadership variables on outcome variables; transformational leadership had a significantly greater influence on outcome variables than transactional leadership (0.155), as measured by its standardized beta coefficient (0.828). These findings explained 0.94 of the variance in the R-squared value. Laissez-faire was dropped from the model due to its insignificance. Between laissez faire and administration by passive exception, substantial inverse bivariate correlations were discovered for all model subscales; nevertheless, a significant positive correlation was found between them. Cronbach's Alpha reliability coefficients greater than.70 and discriminant validity coefficients greater than 0.90 were achieved for each of the model's subscales. Despite growing global interest in transformational leadership, limited empirical evidence exists from Latin American contexts, particularly within Mexican educational institutions. This study addresses that gap, providing culturally relevant insights into how leadership styles can be leveraged to enhance organizational performance in public schools.